The detective's assistant - Hannigan, Kate (Little, Brown and Company, 2016)
In 1859, eleven-year-old Nell goes to live with her aunt, Kate Warne, the first female detective for Pinkerton's National Detective Agency. Nell helps her aunt solve cases, including a mystery surrounding Abraham Lincoln, and the mystery of what happened to Nell's own father.